Mycotoxins in milk: Occurrence and evaluation of certain detoxification attempts - Youssef, Nesrine H.; El Gammal, Mohamed H.; Altaie, Hayman A. A.; Qadhi, Alaa; Tufarelli, Vincenzo; Losacco, Caterina; Abd El‐Hack, Mohamed E.; Abdelsalam, Nader R. (Food science & nutrition, 2023)
Milk contaminated with mycotoxins is a significant issue affecting human health, especially in infants. The current study aimed to investigate the presence of mycotoxins in milk collected from women farmers' vendors (WFV), and to evaluate certain herbal plant fibers as green mycotoxin binders. Moreover, explore the binding efficiency ratios of mycotoxins using shaking or soaking process incorporated with herbal extracts. Furthermore, compare the taste evaluations of tested milk are enriched with herbal extracts. Results indicated that the fumonisins were not detected in the collected cow milk samples but realized a 25% occurrence ratio in buffalo's milk samples. A high occurrence ratio of aflatoxin M1 (aflaM1) was observed in buffalo and cow milk samples. The soaking process of plant fibers in contaminated milk overnight significantly degrades and adsorbs mycotoxins particles. The shacking process incorporated with plant fibers exhibited more effectiveness in mycotoxins degradation than soaking or shacking processes alone. The speed of shacking process played an important role in the mycotoxin's binding process. All the tested plant fibers effectively reduced all mycotoxin presence in contaminated milk, especially green tea, during the soaking or shacking process. Moreover, the shacking process incorporated with plant fibers promoted and supported the mycotoxins degradation process. Milk contaminated with mycotoxins is a highly significant issue affecting human health. The study investigated the role of the shacking process on plant fibers binding process. The shacking process with plant fibers promoted and supported the mycotoxins degradation process.